Converting energy from overhead transmission line vibrations using a low-frequency and low-amplitude harvester in a smart grid - Tan, Yisong; Li, Shixun; Zhang, Wenqiang; Wang, Shuqing; Zhou, Yang; He, Yutong; Ren, Limin (Frontiers in Energy Research, 2023)
Introduction: Overhead transmission line vibration is detrimental to the normal operation of the power grid. It is necessary to remotely monitor overhead transmission lines with sensors in normal operation, and sensors require a constant source of energy. Harvesting energy from transmission line vibrations is an excellent solution to power these sensors. Methods: A low-frequency and low-amplitude vibration energy harvester is proposed, analyzed, produced and experimented in this study. A main constituent of the energy harvester is an outer support, an inner support, four one-way bearings, a bevel gear system and a DC generator. The harvester converts the linear reciprocating motion of the line into reciprocating swing at first and then converts it into fixed-direction rotation. Theoretical analyses are conducted to determine the harvester performance factors. Finally, the harvester is fabricated and tested. Results: The test results are in good accordance with the simulation results. At the vibrating speed as 0.48 m/s, the maximum output power and output voltage are 4.2 W and 24.7 V, respectively. The weather sensor and video recorder installed on the transmission line are powered by the harvester. Discussion: The energy harvester also effectively suppresses the vibration of transmission lines and has great potential in the constructions of smart grids. The harvester provides a feasible solution for harvesting line vibration energy and suppressing line breeze vibration simultaneously.